DESAIN ALAT PENGERING IKAN TIPE EFEK RUMAH KACA DI DESA KUALA LEUEGE PEREULAK ACEH TIMUR - Fajri, Rahmatul; Jofrishal; Tri Anda, Sabrian; Nucifera, Prima (Fakultas Teknik, Universitas Samudra, 2024)
The community service that has been carried out aims to improve the economy of the Kuala Leuge Pereulak village community in East Aceh through processing local community catches with effective and appropriate fish drying. The method of implementing the service carried out is through socialization and education regarding the effective use of marine products through the sale of dried fish or salted fish using good and effective drying. The outcome of the program that has been carried out has a positive impact on the community in Kuala Leuge village, which can improve the community's economy through training from activities carried out by the community, making it easier to dry fish that will be marketed.